Energiepark Mainz: Technical and economic analysis of the worldwide largest Power-to-Gas plant with PEM electrolysis. (11th May 2017) - Kopp, M.; Coleman, D.; Stiller, C.; Scheffer, K.; Aichinger, J.; Scheppat, B.
Abstract: The following paper is an analysis of the operating experiences during the initial phase of the 6 MW PEM electrolysis project "Energiepark Mainz". The paper is divided into a technical and an economic evaluation. The technical evaluation contains the calculation of the efficiency of the Power-to-Gas plant based on the total power consumption, as well as the energy utilization factor. The economic evaluation analyses the different options of electricity procurement for the electrolysis. The three options, electricity purchase at the European power exchange, excess electricity from a direct marketing company, and participating in the control reserve market have been analysed. One first outcome shows, that economic feasibility can mainly be improved through participation in the secondary control reserve market. Highlights: First operational results of the worldwide largest Power-to-Gas plant with PEM electrolysis. Evaluation of different options of electricity procurement. Analysis of the utilization of surplus electricity from renewable sources. Analysis of the participation in the control reserve market of PtG plants.